2018
DOI: 10.1186/s12915-018-0530-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of long single-stranded DNA donors in genome editing: generation and validation of mouse mutants

Abstract: BackgroundRecent advances in clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) genome editing have led to the use of long single-stranded DNA (lssDNA) molecules for generating conditional mutations. However, there is still limited available data on the efficiency and reliability of this method.ResultsWe generated conditional mouse alleles using lssDNA donor templates and performed extensive characterization of the resulting mutations. We observed that the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 30 publications
5
97
0
1
Order By: Relevance
“…Clrn2 clarinet /+ carrier mice were subsequently backcrossed to C57BL/6J for ten generations until congenic. The Clrn2 del629 mutant line was generated on a C57BL/6N background by the Molecular and Cellular Biology group at the Mary Lyon Centre (MLC), MRC Harwell Institute using CRISPR‐Cas9 genome editing (Mianne et al , ; Codner et al , ) (). Within the MLC, all mice were housed and maintained under specific pathogen‐free conditions in individually ventilated cages, with environmental conditions as outlined in the Home Office Code of Practice.…”
Section: Methodsmentioning
confidence: 99%
“…Clrn2 clarinet /+ carrier mice were subsequently backcrossed to C57BL/6J for ten generations until congenic. The Clrn2 del629 mutant line was generated on a C57BL/6N background by the Molecular and Cellular Biology group at the Mary Lyon Centre (MLC), MRC Harwell Institute using CRISPR‐Cas9 genome editing (Mianne et al , ; Codner et al , ) (). Within the MLC, all mice were housed and maintained under specific pathogen‐free conditions in individually ventilated cages, with environmental conditions as outlined in the Home Office Code of Practice.…”
Section: Methodsmentioning
confidence: 99%
“…Here we injected lssDNA, not dsDNA, and we do not know how lssDNA behaves in injected Xenopus embryos as opposed to injected dsDNA that can persist (at least somatically) in adults and often exists as tandem head‐to‐tail concatemers integrated in the genome (Etkin & Pearman, 1987 and references therein). In mice, it has been shown that random insertions of injected lssDNA into the genome could also occur (Codner et al, 2018). Because of these results, we tested whether any evidence of germline transmission of randomly integrated lssDNA can be observed in albino embryos obtained from the F0 “Female 1” crossed with an albino male.…”
Section: Resultsmentioning
confidence: 99%
“…The first thing to take into account after an experiment involving CRISPR-Cas9 tools is the genetic noise (variability) produced by the endogenous repairing systems, particularly the non-homologous end joining pathway. No matter what you do, or what tricks you implement, you are going to be dealing with mosaic founder mice, whose complexity can vary enormously (Codner et al, 2018;Seruggia, Fernández, Cantero, Pelczar, & Montoliu, 2015). The CRISPR-Cas9 reagents, deposited (microinjected or electroporated) in mouse fertilized oocytes, will remain active for several cell divisions.…”
Section: Methods 1: Genotyping Genome-edited Mice To Detect Your Allelmentioning
confidence: 99%